Esophageal fistula in steers - Raiser, Alceu Gaspar (Pesquisa Agropecuaria Brasileira, 2014)
A surgical technique for establishment of esophageal fistula is described in ten steers in order to detail the surgical procedure and to analyse the postoperative behaviour for twelve months. The operation in a steer can be completed in about forty minutes. Postoperative complications have required constant monitorization.